Interaksi Motivasi Belajar Tinggi Serta Rendah Versus Hasil Belajar Materi Perkakas Tangan - Heri Yudianto; Rufi’i Rufi’i; Ibut Priono Leksono (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2022)
This research aims to research high and low learning motivation versus learning outcomes hand tool material. This research apply the Quasy Experiment method. While the research design is a 2 x 2 factorial. Furthermore, for the data collection method using the cluster random sampling method. The sample of research was 144 students. Furthermore, several series of tests were held, including: validity test, reliability test, prerequisite test (test of homogeneity, normality, and one way ANOVA) and hypothesis testing (two way ANOVA test). This questionnaire consists of 36 questionnaires so that the highest is 144 and the lowest is 36. From scores obtained, it can be grouped into 2 categories, namely students with low motivation and high motivation categories. Students with low motivation category if they get a score between 36-89 and students with high motivation category if they get a score between 90-144. All samples in this study were given a learning motivation questionnaire and then grouped according to the categories of students with high learning motivation categories and students with low learning motivation categories. The results of this research show that there is a comparison between students who have high learning motivation and students who have low learning motivation on the learning outcomes of hand tools in class X SMKN 1 Driyorejo and SMKS YPM 8 Sidoarjo in the 2021-2022 academic year.